Estratégias de controle para correção da distorção harmônica da corrente de entrada do retificador Boost em MCD entrelaçado em série - Orsi, Gustavo Cardoso (2019)
This work proposes two control techniques based on variable duty-cycle for the serial interleaved boost rectifier. The purpose of the control strategies is to increase the power factor and efficiency of the rectifier by eliminating the harmonic distortion of the input current, which is characteristic of this converter as it consists of two boosts operating in discontinuous conduction mode. At first, it is presented a bibliographic review about solutions used in similar topologies, as well as recent works that used this rectifier. Next, for each strategy, an evaluation of the operation is performed, as well as mathematical analysis, design methodology and validation of results through simulations and bench tests. The results are compared with the requirements of IEC 61000-3-2 and with the rectifier without any correction technique. The two control techniques proposed are simple to implement and presented great improvement in current harmonic distortion compared to the classical converter, easily complying with the requirement of the standard used.